AKTIVITAS ANTIOKSIDAN DAN ANTIMIKROBA SARANG BURUNG WALET (Collocalia Fuciphaga) DARI BERBAGAI JENIS KELAS SARANG DAN JENIS BANGUNAN - Andi Syahid Khalid Assegraff; Wiwin Suwinarti; Isna Yuniar Wardhani; Agus Sulistyo Budi; Irawan Wijaya Kusuma; Enos Tangke Arung (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2024)
The community has traditionally utilized the swallow’s nest (Collocalia fuciphaga), an edible bird’s net (EBN), as a component in medicines and cosmetics. Within the cave’s walls lies the environment for the swallow’s nest. The nest’s quality and form are taken into account when determining the nest wallet’s selling price. This study intends to ascertain the possible suppression of the bacteria Staphylococcus sp. and Escherichia sp. activity as well as the antioxidant activity of the swallow’s nest from the nest class formed from wood and concrete construction types. The study was conducted directly on dry, hair- and dirt-free, finely powdered, and dissolved in distilled water swallow nests (Collocalia fuciphaga). Testing for antibacterial activity was conducted. Agar well testing for antibacterial activity was carried out using Mueller Hinton Agar (MHA) and chloramphenicol media as positive controls. Ascorbic acid was used as a positive control while 1,1-diphenyl-2-picrylhydrazyl (DPPH) was tested for its ability to scavenge free radicals. The test findings demonstrated that the swallow (Collocalia fuciphaga) had substantial antioxidant activity against DPPH and that the swallow’s nest (Collocalia fuciphaga) had antibacterial activity against Staphylococcus sp. and Escherichia sp. germs. The swallow’s nest’s (Collocalia fuciphaga) antioxidant and antibacterial properties are specific to different nest classes and building kinds, so they may be utilized as a foundation for thought about raising the selling price of bowls, powders, and crumbles in each form of structure.